2009
DOI: 10.1007/s12529-008-9011-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitively Oriented Behavioral Rehabilitation in Combination with Qigong for Patients on Long-Term Sick Leave Because of Burnout: REST—A Randomized Clinical Trial

Abstract: This study showed no differences in effect between CBR and Qigong compared with Qigong only in a per-protocol analysis. Both rehabilitation programs showed positive effect for patients with burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 37 publications
4
66
0
5
Order By: Relevance
“…Moreover, only individual treatment programs were evaluated. After group cognitive-behavioural therapy combined with Qigong, compared to Qigong only, more than half the burnout patients on long-term sick leave in both programmes showed at least a partial RTW after one year, while 40% were still on full-time sick leave [4]. A stress management intervention compared to CAU, in women with work stress-related sick leave in a company health care unit, resulted in only 40% RTW for both groups, as long as 5 years after the intervention [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, only individual treatment programs were evaluated. After group cognitive-behavioural therapy combined with Qigong, compared to Qigong only, more than half the burnout patients on long-term sick leave in both programmes showed at least a partial RTW after one year, while 40% were still on full-time sick leave [4]. A stress management intervention compared to CAU, in women with work stress-related sick leave in a company health care unit, resulted in only 40% RTW for both groups, as long as 5 years after the intervention [18].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few controlled studies evaluating treatment programs for persons on sick leave due to work stress-related mental illness have been published [3,4]. As a rule, the interventions studied were oriented towards the individual and were of the cognitive-behavioural therapy (CBT) type, aiming to improve stress management.…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that all stress-management interventions are effective even though cognitive-behavioural interventions are the most effective. A randomized clinical trial studying patients on long-term sick leave due to burnout compared a cognitively oriented behavioural rehabilitation in combination with qigong with rehabilitation that only consisted of qigong and found both interventions to be equally effective (19). Heiden et al (10) compared cognitive behavioural training, physical activity, and traditional care for people with stress-related disorders in a randomized controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous Swedish studies have shown that employees with CMDs may seek treatment on their own, especially if they are aware that they belong to the control group [46, 47]. To detect possible treatment bias of this sort, items on co-interventions have been included in the questionnaires to the employees.…”
Section: Discussionmentioning
confidence: 99%